The Relationship Between the Triglyceride-Glucose Index and Cryptogenic Stroke in Patients with Patent Foramen Ovale - Fatma Esin MD; Hüseyin Sefa Ince MD; Semih Aktürk MD; Fahrettin Tugrul Citekci MD; Aykan Celik MD; Ugur Kocabas MD; Tuncay Kiris MD; Mustafa Karaca MD (Clinical and Applied Thrombosis/Hemostasis)
Objective This study aimed to investigate the association between the triglyceride-glucose (TyG) index and cryptogenic stroke (CS) in patients diagnosed with patent foramen ovale (PFO) using transesophageal echocardiography (TEE). Methods A retrospective, single-center study was conducted at a tertiary education and research hospital from January 2015 to December 2023. The study population included 1017 consecutive patients with sinus rhythm diagnosed with PFO, of whom 210 had CS. The TyG Index was calculated using triglyceride and fasting glucose levels. Results Patients with CS were older (47.53 ± 12.34 years) compared to control group (44.40 ± 17.82 years, p = .005). The proportion of males was higher in the CS group (56.2%) compared to the control group (48.3%, p = .042). Laboratory findings revealed higher TyG Index (8.87 ± 0.51 vs 8.63 ± 0.55, p < .001) in patients with CS. TyG Index was an independent predictor of CS in patients with PFO (OR: 2.832, 95%CI: 1.979-4.053 p < .001). Conclusion Elevated TyG Index levels was associated with CS in patients with PFO. The TyG index may serve as a useful biomarker for assessing CS risk in this population.